2016
DOI: 10.1097/01.aoa.0000489491.73090.08
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Conventional Digital Palpation and Ultrasound of the Cricothyroid Membrane in Obese Women in Labour

Abstract: Summary Success of cricothyroidotomy depends on accurate identification of anatomical neck landmarks. Anaesthetists palpated the cricothyroid membrane of 28 obese and 28 non‐obese women in labour (cut‐off BMI 30 kg.m−2) and marked the entry point for device insertion with an ultraviolet invisible pen. Ultrasonography was used to mark the midpoint of the cricothyroid membrane and the distance between the two marks was measured. The median (IQR [range]) distance between the two marks was significantly greater in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…Rev Chil Anest 2016; 45: [16][17][18][19][20][21][22][23][24][25][26] Las razones detrás de este cambio pueden incluir:…”
Section: Figuraunclassified
“…Rev Chil Anest 2016; 45: [16][17][18][19][20][21][22][23][24][25][26] Las razones detrás de este cambio pueden incluir:…”
Section: Figuraunclassified
“…[8][9][10][11][12][13] Ces études se fondent sur des méthodologies semblables afin de déterminer la fréquence à laquelle les médecins évaluateurs ont correctement localisé la membrane cricothyroïdienne par palpation externe. Les estimations des évaluateurs dans ces études (tout comme dans l'étude publiée ici) ont été comparées à Deficiencies in locating the cricothyroid membrane by palpation 793 l'emplacement réel de la membrane cricothyroïdienne déterminé par échoguidage.…”
Section: Incapables De Localiser Launclassified
“…[8][9][10][11][12][13] These studies used similar methodologies to determine how often physician assessors correctly identified the location of the CTM by external palpation. The assessors' estimations in these studies (and similarly in the present one) were compared with the actual location of the CTM as confirmed by ultrasound.…”
mentioning
confidence: 99%
“…The 4th National Audit Project similarly identified a 64% failure rate of when anaesthetists utilised this 'rescue' technique [23]. This may in part be related to anaesthetists' relatively poor ability to correctly identify the cricothyroid membrane [24,25]. In one study, physician accuracy in identifying the cricothyroid membrane was 10 of 41 in non-obese female subjects but none of 15 obese subjects [24].…”
Section: Airway Managementmentioning
confidence: 99%
“…Studies investigating ultrasound localisation of the cricothyroid membrane have produced some encouraging results. In a study in labouring women, anaesthetists palpated and identified the cricothyroid membrane of obese and non-obese women [25]. Ultrasonography was then used to assess the accuracy of digital palpation.…”
Section: Airway Managementmentioning
confidence: 99%